In situ measurements of molecular iodine in the marine boundary layer: the link to macroalgae and the implications for O3, IO, OIO and NOx - Huang, Ru-Jin; Seitz, Katja; Buxmann, Joëlle; Pöhler, Denis; Hornsby, K. E.; Carpenter, L. J.; Platt, Ulrich; Hoffmann, T. (Atmospheric chemistry and physics, 2010)
Discrete in situ atmospheric measurements of molecular iodine (I2) were carried out at Mace Head and Mweenish Bay on the west coast of Ireland using diffusion denuders in combination with a gas chromatography-mass spectrometry (GC-MS) method. I2, IO and OIO were also measured by long-path differential optical absorption spectroscopy (LP-DOAS). The simultaneous denuder and LP-DOAS I2 measurements were well correlated (R2=0.80) but the denuder method recorded much higher concentrations. This can be attributed to the fact that the in situ measurements were made near to macroalgal sources of I2 in the intertidal zone, whereas the LP-DOAS technique provides distance-averaged mixing ratios of an inhomogeneous distribution along the light-path. The observed mixing ratios of I2 at Mweenish Bay were significantly higher than that at Mace Head, which is consistent with differences in local algal biomass density and algal species composition. Above algal beds, levels of I2 were found to correlate inversely with tidal height and positively with the concentrations of O3 in the surrounding air, indicating a role for O3 in the production of I2 from macroalgae, as has been previously suggested from laboratory studies. However, measurements made ~150 m away from the algal beds showed a negative correlation between O3 and I2 during both day and night. We interpret these results to indicate that the released I2 can also lead to O3 destruction via the reaction of O3 with I atoms that are formed by the photolysis of I2 during the day and via the reaction of I2 with NO3 radicals at night. The results show that the concentrations of daytime IO are correlated with the mixing ratios of I2, and suggest that the local algae sources dominate the inorganic iodine chemistry at Mace Head and Mweenish Bay.